2019
DOI: 10.1177/2332858419879439
|View full text |Cite
|
Sign up to set email alerts
|

Stress in Boom Times: Understanding Teachers’ Economic Anxiety in a High-Cost Urban District

Abstract: Despite growing concern over teachers’ ability to live comfortably where they work, we know little about the systematic relationship between affordability and teachers’ well-being, particularly in high-cost urban areas. We use novel survey data from San Francisco Unified School District to identify the patterns and prevalence of economic anxiety among teachers and assess how this anxiety predicts teachers’ attitudes, behaviors, and turnover. We find that San Francisco teachers have far higher levels of economi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Female teachers face twice as much anxiety compared to their male counterparts (Lizana & Lera, 2022). This is because they had to balance between their family affairs and work affairs (Desouky & Allam, 2017;Atabek et al, 2019;Budyawati & Utami, 2019;Dizon-Ross et al, 2019;Ng et al, 2019;Othman & Sivasubramaniam, 2019;Bete et al, 2020;Li et al, 2020;Ratanasiripong et al, 2020;Ozamiz et al, 2021;Santamaría et al, 2021;Lizana et al, 2021;Wakui et al, 2021;Yoo et al, 2021;Gawrych et al, 2022;Spadafora et al, 2022). Jakubowski & Sitko (2021) in their study found that female teachers in Poland are more likely to have anxiety and depression as the culture of the country still associates managing household to be a full responsibility of a female.…”
Section: Independent Factormentioning
confidence: 96%
See 1 more Smart Citation
“…Female teachers face twice as much anxiety compared to their male counterparts (Lizana & Lera, 2022). This is because they had to balance between their family affairs and work affairs (Desouky & Allam, 2017;Atabek et al, 2019;Budyawati & Utami, 2019;Dizon-Ross et al, 2019;Ng et al, 2019;Othman & Sivasubramaniam, 2019;Bete et al, 2020;Li et al, 2020;Ratanasiripong et al, 2020;Ozamiz et al, 2021;Santamaría et al, 2021;Lizana et al, 2021;Wakui et al, 2021;Yoo et al, 2021;Gawrych et al, 2022;Spadafora et al, 2022). Jakubowski & Sitko (2021) in their study found that female teachers in Poland are more likely to have anxiety and depression as the culture of the country still associates managing household to be a full responsibility of a female.…”
Section: Independent Factormentioning
confidence: 96%
“…Therefore, an abundance is tasks accumulated by teachers leads them to be constant under pressure from many parties ( Furthermore, the subfactor of teaching knowledge is also closely related to the teacher's tendency to anxiety and depression. This is because teachers who are incompetent in pedagogy and content knowledge will have low self-esteem making them to be living in fear that causes anxiety and depression in themselves (Desouky & Allam, 2017;Ramirez et al, 2018;Alvites et al, 2019;Dizon-Ross et al, 2019;Ganley et al, 2019;Oguzhan et al, 2019;Thomas & Sari, 2019;Othman & Sivasubramaniam, 2019;Li et al, 2020;Syuhada & Retnawati 2020;Bete et al, 2020;Genoud & Waroux, 2021;Pressley et al, 2021;Wakui et al, 2021;Gawrych et al, 2022;Spadafora et al, 2022).…”
Section: Occupational Factormentioning
confidence: 99%
“…For instance, while gentrification and the associated effects have brought significant changes to many central city neighborhoods, the effects have often been quite varied (Pearman, 2019). Most relevant to this study is the extent to which increased housing prices and loss of affordability displaces individuals who grew up attending district schools but have little potential of becoming teachers in the district because of a loss of affordability (Dizon-Ross et al, 2019).…”
Section: Limitationsmentioning
confidence: 99%
“…Rarely does this literature draw direct comparisons between teachers and observationally similar professionals in other lines of work, which raises the question of whether teaching uniquely affects (or selects on) the mental health of its professional workforce. Moreover, changes in both policies governing public schools and the relative prestige and real wages of teaching over time (Allegretto & Mishel, 2016;Dizon-Ross, Loeb, Penner, & Rochmes, 2018) suggests that teachers' mental health, relative to their peers, might have changed over time.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence from San Francisco suggests teachers facing high costs of living report more economic anxiety than teachers elsewhere, which fuels negative views of teaching and higher rates of absence (Dizon-Ross et al, 2018). Indeed, a variety of policy changes in the United States, at the state and federal level, increased the credentials required for teaching and added a variety of accountability measures tied to student achievement (Dee & Jacob, 2010;Firestone, 2014).…”
Section: Introductionmentioning
confidence: 99%